LEVEL OF COMMUNITY PARTICIPATION IN LAKSANA TOURISM VILLAGE, IBUN DISTRICT, BANDUNG REGENCY, WEST JAVA, INDONESIA - Serly Anjelia; Endah Djuwendah; Elly Rasmikayati; Hepi Hapsari (Institut Pariwisata dan Bisnis Internasional, 2020)
Laksana Tourism Village has the potential to become a better tourist destination. The situation shows that the management of community-based tourism villages is not good enough. This study aims to determine the level of community participation. This study uses a quantitative approach with survey techniques. The object analyzed is the community involved in tourism activities. The data analyzed are the results of interviews, questionnaires, literature studies, and field documentation. Research data were analyzed using descriptive statistics with a Likert scale. The results of this study are that community participation in the Tourism Village at the planning stage is still dominated by external parties and certain groups of people, at the implementation stage it involves almost the entire community, the utilization stage of the results shows there is a clear profit sharing but not yet transparent report, and at the evaluation stage there is no continuous evaluation.